Comparative Analysis of Antimicrobial Activities of 43 Trichoderma Isolates Against Sclerotium rolfsii, the Pathogen Causing Collar Rot Disease in Elephant Foot Yam - Joseph, Linet K; S. S., Veena; G., Byju; J., Sreekumar; S., Karthikeyan (JOURNAL OF ROOT CROPS, 2020)
Elephant foot yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) is an important tuber crop which is popular as a food security crop as well as a remunerative cash crop. The crop is preferred in tropical and sub-tropical regions due to its high production potential (50.80 t ha-1), market acceptability and lucrative economic returns. Collar rot caused by Sclerotium rolfsii is the most destructive and predominant disease causing great crop loss. Application of Trichoderma spp is recommended as the eco-friendly strategy to combat the crop loss. However, all Trichoderma isolates may not perform equally against specific soil borne pathogens as Trichoderma antagonists have different mechanisms of pathogen recognition. The present study was conducted with an objective of identifying most potent isolates against Sclerotium rolfsii from the collection of Trichoderma isolates (43 nos.) obtained from tuber crop ecosystem during the period 2010-2018. The differential antagonistic potential of the isolates were assessed by adopting three in vitro screening methods viz., direct confrontation, antibiosis test based on production of diffusible inhibitory metabolites and production of volatile compounds. In dual culture method, percentage inhibition of mycelial growth of pathogen varied from 9.44% (isolate T26) to 82.32% (isolate T32). The percentage inhibition ranged from 3.70% (isolate T31) to 100% (30 isolates had 100% inhibition) in antibiosis test based on production of diffusible inhibitory metabolites by isolates against pathogen. Comparatively low inhibition was noticed with volatile compounds produced by isolates against pathogen. Percentage inhibition of mycelial growth of pathogen varied from 15.38% (isolate T26) to 42.96% (isolate T31). To identify the most potent isolates, additive inhibition effect by the isolates were calculated and statistically analysed by SAS statistical software (SAS2010 - SAS Institute Inc., Cary, North Carolina, USA.). Based on the additive effect as well as results obtained from different methods, it was concluded that the isolates, T38, T36, T32, T40 and T6 have excellent potential to be used as bio-control agents to mitigate the crop loss caused by S. rolfsii. These isolates may be tested in field conditions for their field performance as well as for survival in soil before recommending to farmers.